Shariah-Compliant E-Payment Framework in Malaysia: Integrating Fiqh, Digital Security and Regulatory Governance - Mohd Zulkifli Muhammad; Fatihah Mohd; Tamrin Amboala; Hanudin Amin; Wan Fatin Fatihah Yahya; Muhammad Khalilur Rahman; Azila Jaini; Mohammad Salim Al-Rawashdeh (Universiti Sains Islam Malaysia, 2025)
Journal of Fatwa Management and Research, Volume 30 Issue 2 Page (34–54)